Change Management PT Pal Indonesia (Persero) Dealing With a Strategic Environment in the Vuca Era - NOFRIZA, Dodi; SIMBOLON, Luhut; SUSANTO, Susanto (PT Keberlanjutan Strategis Indonesia, 2024)
Changes that occur very quickly and dynamically in the VUCA Era encourage the need for an effective management system to achieve company goals and solve all challenges, both internal and external. PT PAL Indonesia (Persero) is a strategic industry that produces the main tools of the Indonesian defense system, especially for the marine dimension. It also needs to have strategies in dealing with the strategic environment in the VUCA Era. The purpose of this study is to analyze how change management is carried out by PT PAL Indonesia (Persero) in dealing with the Strategic Environment in the VUCA Era. The method of writing scientific articles is using qualitative research methods and data collection techniques in the form of Literature Studies and Library Research. The results of the study explain that the Maritime Industry Transformation 4. 0 is PT PAL Indonesia's effort in responding to VUCA's challenge to increase the company's business competition. PT PAL Indonesia's HR management through increasing core capability and people competency is an important capital in realizing Maritime Industry Transformation 4.0.